Chapter Caterina Colombini e le origini della congregazione delle gesuate - Nardi, Paolo (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The results of new archival research, compared with some epistles of Blessed Giovanni Colombini, allowed to frame the mystical experience of his cousin Caterina Colombini, which matured in the Sixties of the fourteenth century, in a situation of serious breakdown with his family, caused by patrimonial reasons. Caterina succeeded, also with the help of some friends of her cousin, to free herself from the family context and to constitute the first community of Gesuate, so-called because they observed the same way of life as the Gesuati, then in 1371 to equip this congregation with a residence purchased with her own money in the Sienese district of Vallepiatta and finally to submit it to the protection and jurisdiction of the female Benedictine monastery of Saints Abondio and Abondanzio near Siena. Thus a new female congregation was born, that also spread to other cities in Italy, but it did not turn into a religious order, while avoiding the accusation of heresy for "beguinage".